(untitled) (ItalianoLinguadue, 2025)
Key competences for the vertical curriculum: teachers’ opinions and teaching materials In this contribution we present the first results of a qualitative survey, carried out in schools in Tuscany, which aimed to verify what knowledge and importance is given in the educational sphere to the Key Competences for Lifelong Learningdescribed by the 2006 European Recommendation and updated by the 2018 Recommendation, and whether there is systematic planning on these competences within schools and whether the conditions are in place for their effective development from a vertical and transversal perspective across the various disciplines. Furthermore, in order to detect any references to the vertical development of the skills taken into consideration, some Italian textbooks used in the last year of primary school and the first year of secondary school were examined. On the basis of the data collected, it emerges that the key competences investigated represent for the teachers interviewed valid inspiring principles useful for the realisation of educational pathways in various school orders; transversality and verticality are considered important elements for the development of these competences. However, it also emerges that a ‘vertical’ approach is very complex to implement for logistical and organisational reasons and due to the lack of specific training that can foster constructive dialogue between groups of teachers with different competences and disciplinary objectives. With regard to the textbooks examined, they show several shortcomings in fostering the full development of key competences insofar as they are still tied to a traditional linguistic and pedagogical framework and, in general, there are no indications of the progressive and vertical development of competences.